Ang pagpapahalagang moral at espiritwal sa relasyong pangkapwa mula sa pilosopikal na pananaw - Ortinero, Aniceta M. (Education quarterly.)
This paper explains the historical origin and the nature of two major components of values education: the moral and spiritual. The author highlights the humanitarian theory of moral ethics and analyzes the seven fundamental and supreme criteria of the moral and binding relationship between the moral and spiritual.